CROSSING BORDERS: STORIES OF TRANSNATIONALS BECOMING ENGLISH LANGUAGE TEACHERS IN MEXICO - Irasema Mora Pablo; M. Martha Lengeling; Nora Margarita Basurto Santos (Signum: Estudos da Linguagem, 2015)
The data in this article come from a two-year study that examines the transnational immigrant lives of young adults whose families resided for a number of years in the United States, always maintaining close ties to their country of origin, Mexico, until they decided or were forced to return. These participants acquired English as children of Mexican immigrants in the United States. Using a narrative approach, findings depict how immigrant students shaped their identities through ambivalent feelings towards both countries and how this identity construction shaped their interest in becoming English teachers or rejecting the language to the point that they forgot the language they had learned in the United States. Their transnational experiences of living in and between two countries appeared to be at the forefront of their construction of identity, defining who they are and who they want to be. This work suggests that transnationals possess an important cultural and linguistic capital that they use to their advantage in order to fit in in their own country of origin.